2016
DOI: 10.3390/molecules21050564
|View full text |Cite
|
Sign up to set email alerts
|

Agrimonia eupatoria L. and Cynara cardunculus L. Water Infusions: Comparison of Anti-Diabetic Activities

Abstract: Diabetes mellitus (DM) is frequently diagnosed at a time when patients already suffer from several cardiovascular complications. Our previously published data (Molecules 201520 (11): 20538-50) on the anti-oxidative properties of Agrimonia eupatoria L. (AE) and Cynara cardunculus L. (CC) prompted us to extend the available evidence on their possible protective activities on selected DM-related parameters in a streptozotocin-induced DM rat model and in a series of in vitro experiments. Male rats were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 47 publications
(87 reference statements)
1
23
0
Order By: Relevance
“…In fact, we found in subjects from the Altilix ® supplemented vs. placebo groups, regarding MetS comorbidities, a significant improvement in glucose metabolism parameters (including HbA1c, insulin resistance, and pancreatic β-cell function), in agreement with some in vitro and in vivo literature data [34,35,36]. In particular, among these, some in vivo studies with oral daily administration of Cynara cardunculus (L.) subsp.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In fact, we found in subjects from the Altilix ® supplemented vs. placebo groups, regarding MetS comorbidities, a significant improvement in glucose metabolism parameters (including HbA1c, insulin resistance, and pancreatic β-cell function), in agreement with some in vitro and in vivo literature data [34,35,36]. In particular, among these, some in vivo studies with oral daily administration of Cynara cardunculus (L.) subsp.…”
Section: Discussionsupporting
confidence: 88%
“…Other studies reported in 39 overweight subjects, that the intake of tablets containing extract of artichoke during meals, resulted in a significant reduction of the HOMA index [34]. Whereas, in vitro studies evidenced the role of chlorogenic acid on glucose regulation—antagonist in glucose transport, inhibitor of α-amylase and α-glucosidase, and therefore in the post-prandial glucose blood concentration [34,35,36]. We also found, after Altilix ® supplementation, an improvement in both HOMA-IR (marker of insulin resistance), a marker useful in identifying individuals with metabolic NAFLD [37] and HOMA-β (marker of pancreatic β-cell function).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the data obtained we decided to choose A. asiatica as the herb for further investigation. In addition, there is information about the antidiabetic activity of the genus Agrimonia in the literature [ 30 , 31 ]. The chemical composition of this plant species is insufficiently studied.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the previous studies showing that C. cardunculus L. or C. scolymus L. have antidiabetic properties. [ 36 37 ] Furthermore, a recent study by Heidarian and Soofiniya showed that the ALE administration in doses of 200 and 400 mg/kg b.wt to the streptozotocin-induced diabetic rats led to a significant reduction in their blood glucose levels. [ 38 ]…”
Section: Discussionmentioning
confidence: 99%